Numerical solution of one-dimensional differential equations by weighted residual method using Bernoulli wavelets - Lingaraj Angadi (Computational Algorithms and Numerical Dimensions)
This paper presents the method of solving one-dimensional differential equations through the weighted residual technique, employing Bernoulli wavelets as the basis functions. These wavelets serve as the foundation for the calculation of numerical solutions for one-dimensional differential equations. The numerical outcomes are contrasted with those from current techniques and the precise solution. A selection of numerical test problems is included to demonstrate the practicality and efficiency of the proposed approach.